1983
DOI: 10.1093/oxfordjournals.eurheartj.a061401
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics during emotional stress in borderline and mild hypertension

Abstract: The hemodynamic response to emotional stress (mental arithmetic) was studied in ten borderline and ten mild hypertensives in comparison to ten age-matched normotensives. Due to emotional stress the blood pressure increased in all three groups; its rise was greater in borderline and mild hypertension. After stress, the blood pressure also remained elevated longer in the hypertensive groups. The increased blood pressure reaction was accompanied by a greater rise of heart rate and cardiac output. The increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

1983
1983
2007
2007

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 20 publications
1
10
1
1
Order By: Relevance
“…Several studies have reported that the mental stress-induced increase in BP is greater in subjects with essential hypertension than in subjects with normal BP (27,28). However, whether the sensitivity of BP to mental stress differs between subjects with borderline hypertension and those with normal BP has not been determined conclusively (29)(30)(31). Our results did not show a statistically significant difference in the sensitivity of SBP to mental stress between subjects with high BP and those with normal BP.…”
Section: Discussioncontrasting
confidence: 78%
“…Several studies have reported that the mental stress-induced increase in BP is greater in subjects with essential hypertension than in subjects with normal BP (27,28). However, whether the sensitivity of BP to mental stress differs between subjects with borderline hypertension and those with normal BP has not been determined conclusively (29)(30)(31). Our results did not show a statistically significant difference in the sensitivity of SBP to mental stress between subjects with high BP and those with normal BP.…”
Section: Discussioncontrasting
confidence: 78%
“…Yet, quite a number of researchers have tested the hypothesis of de layed blood pressure recovery after stress in hypertensives. Whereas Brod et al [15], Innes et al [16], Svensson and Theorell [17], Schulte and Neus [18], Fredrikson and Engel [ 19] could observe delayed recovery of hyper tensives in at least one blood pressure vari able, Lorimer et al [20], Fredrikson et al [11], Jern [10] and Anderson et al [21] found no group differences in blood pressure recovery at all. Delayed recovery of noradrenaline in normotensives (or faster recovery in hyper tensives), as suggested by our results, may be a chance result within the scope of multiple comparisons and does not seem worth inter preting unless after replication.…”
Section: Discussionmentioning
confidence: 99%
“…Hastrup and Light used a reaction time test as well as the cold pressor test. Cold pressor increases blood pressure mainly due to a a-adrenergic vasoconstriction (38) whereas mental arithmetic raises it mainly due to p-adrenergic activation (39). Therefore reactivity to different stressors is not always comparable.…”
Section: Discussionmentioning
confidence: 99%